“COUNTABLE/UNCOUNTABLE NOUNS, SOME/ANY” (Ustozlar uchun, 2025)
This article explores the grammatical concepts of countable and uncountable nouns, as well as the use of determiners “some” and “any” in English. Understanding the distinction between countable and uncountable nouns is essential for forming correct sentences, asking questions, and expressing quantity accurately. Countable nouns refer to individual items that can be counted (e.g., apple, book), while uncountable nouns refer to substances, concepts, or collective items that cannot be counted (e.g., water, information).